Temperature Dependent Current Transport Mechanism in Graphene/Germanium Schottky Barrier Diode - Khurelbaatar, Zagarzusem; Kil, Yeon-Ho; Shim, Kyu-Hwan; Cho, Hyunjin; Kim, Myung-Jong; Kim, Yong-Tae; Choi, Chel-Jong (IEEK PUBLICATION CENTER, 2015)
We have investigated electrical properties of graphene/Ge Schottky barrier diode (SBD) fabricated on Ge film epitaxially grown on Si substrate. When decreasing temperature, barrier height decreased and ideality factor increased, implying their strong temperature dependency. From the conventional Richardson plot, Richardson constant was much less than the theoretical value for n-type Ge. Assuming Gaussian distribution of Schottky barrier height with mean Schottky barrier height and standard deviation, Richardson constant extracted from the modified Richardson plot was comparable to the theoretical value for n-type Ge. Thus, the abnormal temperature dependent Schottky behavior of graphene/Ge SBD could be associated with a considerable deviation from the ideal thermionic emission caused by Schottky barrier inhomogeneities.
Keywords: GE-ON-SI; JUNCTION; VOLTAGE; HEIGHT